KARBON AKTIF TERMODIFIKASI NANOSILVER (Universitas Negeri Semarang, 2016)
Carbon was prepared from dried waste bamboo (Dendrocalamus asper) using chemical activation with KOH. The carbon was prepared with the activating agent in a mass ratio of KOH and dried bamboo (3:1) at 800oC. Using impregnation technique, the bamboo-based activated carbon has developed with modified Ag nanoparticle (Ag-AC) to capture formaldehyde. The Ag-AC has characteristics of moderate surface area of 685 m/g and average pore size of 2.7 nm. The adsorption equilibriums and kinetics of formaldehyde on Ag-AC measured. The influences of initial formaldehyde on adsorption performance have measured in a batch system. The equilibrium data were evaluated by isotherm models of Langmuir, Freundlich, and Temkin. The Langmuir model well describes the adsorptive removal of formaldehyde on Ag-AC in this study. Pseudo-first-order and pseudo-second-order kinetic equations were applied to test the experimental data. The pseudo-second-order exhibited the best fit for kinetic study.